KETERAMPILAN MENYIMAK WAWANCARA SISWA KELAS VII SMP NEGERI 3 GUNUNG TULEH KABUPATEN PASAMAN BARAT DENGAN MENGGUNAKAN MEDIA AUDIO - Suhita, Dewi; Eska, Wirnita; Marni, Silvia (Pendidikan Bahasa Indonesia, 2014)
The background of the problem of this research is there is studenstâ problem VII grade at SMPN 3 Gunung tuleh west pasaman distric in listening. The students of SMP N 3 Gunung Tuleh fell difficult in listening, especially in listening to the interview which was read by the teacher. The purpose of this research to determine the listening skill of interviewing students of VII grade of SMP N 3 Gunung Tuleh west Pasaman through audio media figures on aspects of identity, leader opinion, the background of interview, the purpose of the interview and the content of the interview. The type of this research is a quantitative research that using descriptive method. The instrument used in this research is an essay test. Based on the analysis of data and disscussion of the result of the research concluded as follows: (1) listening skill through audio media interview students in listening figur identify obtain an average value of 7,4 more than enough qualitifications (LDC), (2) Student listening skill through audio media interview in listening to the leaders opinion an average value 5,4 with nearly qualified enaugh (HC), (3) Listening skill interview students thorough audio media interview in the background listening obtain an average value of 7,5 with more than enough qualifications (LDC), (4) Listening skill through students interview though audio media in listening the purpose of interview to getÂ  scored on average 6,7 with sufficient qualifications (C), and (5) Listening skill through audio media interview in listening to the content of the interview obtain an average value of 5,8 with a nearly qualified enough (HC). In generally, listening skill in VII grade at SMP N 3 Gunung tuleh districts of west pasaman through audio media relatively more than enough (LDC) with an average value of the average 71,07.